2014
DOI: 10.1021/ar400286b
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective 1,3-Dipolar Cycloadditions of Azomethine Ylides for Biology-Oriented Synthesis

Abstract: ConspectusCycloaddition reactions are among the most powerful methods for the synthesis of complex compounds. In particular, the development and application of the 1,3-dipolar cycloaddition, an important member of this reaction class, has grown immensely due to its powerful ability to efficiently build various five-membered heterocycles. Azomethine ylides are commonly used as dipoles for the synthesis of the pyrrolidine scaffold, which is an important motif in natural products, pharmaceuticals, and biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
126
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 455 publications
(127 citation statements)
references
References 48 publications
0
126
0
1
Order By: Relevance
“…[17] The 2,5-disubstituted pyrrolidine framework is a common structural feature of a large number of alkaloids [17c-e, 18] and also a prototypical template for the development of more powerful catalysts and chiral auxiliaries. [19] This apparently simple heterocyclic structure has been increasingly considered as a new target for the development of stereoselective synthetic processes, and ingenious strategies have been developed in recent years.…”
Section: Resultsmentioning
confidence: 99%
“…[17] The 2,5-disubstituted pyrrolidine framework is a common structural feature of a large number of alkaloids [17c-e, 18] and also a prototypical template for the development of more powerful catalysts and chiral auxiliaries. [19] This apparently simple heterocyclic structure has been increasingly considered as a new target for the development of stereoselective synthetic processes, and ingenious strategies have been developed in recent years.…”
Section: Resultsmentioning
confidence: 99%
“…The 1,3-dipolar cycloaddition reactions between azomethine ylides and dipolarophiles have been recognized as efficient strategies for the synthesis of pyrrolidines with high yields and stereoselectivity. 12 Very recently, we reported that steroidal spirooxindoles (Fig. 1) can potently inhibit the proliferation of several human cancer cells (IC 50 = 0.71 µM against SMMC-7721 cells) and induce apoptosis and cell cycle arrest at G2/M phase in a time-/concentration-dependent manner.…”
Section: Introductionmentioning
confidence: 94%
“…Still, it should at least be indicated that the chief aim of introducing metals in cycloaddition reactions (like everywhere else in organic chemistry) is to arrive at catalytic versions thereof. With the help of chiral metal complexes also optically active [616][617][618][619] and biochemically important compounds [620] could be obtained. In the wake of the discovery of the "click" syntheses, coppercatalyzed enantioselective 1,3-dipolar cycloadditions both of azomethine ylides [618] and azomethine imines [618,621] gained much attention.…”
Section: [3+2]-cycloaddition Reactions Of Metalla-13-dipolesmentioning
confidence: 99%